Theoretical investigation of photophysical properties for a series of iridium(iii) complexes with different substituted 2, 5-diphenyl-1, 3, 4-oxadiazole. (11th January 2016) - Shang, Xiaohong; Li, Yanan; Zhan, Qing; Zhang, Gang
Abstract : A quantum chemical investigation from structural and electronic properties and some charge-transport parameter viewpoints was performed on several homoleptic iridium complexes [(C ∧ N)2 Ir(pic)] with the 2, 5-diaryl-1, 3, 4-oxadia-zoles moiety in C ∧ N ligands, where pic represents the picolinate ancillary ligand. Abstract : A quantum chemical investigation from structural and electronic properties and some charge-transport parameter viewpoints was performed on several homoleptic iridium complexes [(C ∧ N)2 Ir(pic)] with the 2, 5-diaryl-1, 3, 4-oxadia-zoles moiety in C ∧ N ligands, where pic represents the picolinate ancillary ligand. Complex2 exhibits its blue phosphorescent emission with maxima at 485 nm. Furthermore, to obtain the mechanism of high phosphorescence yield in2, we estimated the radiative rate constant k r, the contribution of 3 MLCT in the T1 state, S1 –T1 energy gap Δ E S1 –T1, and the transition dipole moment in the S0 → S1 transition μ S1 for2 . Comparison of calculated results for the four complexes shows that the designed complex2 may possess higher photoluminescent quantum efficiency than the others, making it a potential candidate as an efficient blue-emitting material.